Improvement of the optoelectronic and photovoltaic properties of a cyanopyrid-2, 6-dione-based donor via molecular engineering. (November 2019) - Hundal, Amanpreet Kaur; Agarwal, Anubha; Jameel, Mohammed; Chen, Jing-Yu; Li, Jing-Liang; Jones, Lathe; Kaur, Navneet; Langford, Steven; Gupta, Akhil
Abstract: Through the molecular engineering of cyanopyrid-2, 6-dione functionality, herein we report the design and synthesis of a novel, small molecule electron donor, ( Z )-5-((5'-(4-(diphenylamino)phenyl)-[2, 2′-bithiophen]-5-yl)methylene)-1-(4-(hexyloxy)phenyl)-4-methyl-2, 6-dioxo-1, 2, 5, 6-tetrahydropyridine-3-carbonitrile (coded asCP2 ), which exhibits improved optoelectronic and photovoltaic properties when compared with its structural analogue ( E )-5-((5'-(4-(diphenylamino)phenyl)-[2, 2′-bithiophen]-5-yl)methylene)-1-(2-ethylhexyl)-4-methyl-2, 6-dioxo-1, 2, 5, 6-tetrahydropyridine-3-carbonitrile (coded asCP1 ). The molecular engineering helps to achieve more desirable energy levels together with bathochromic shift in the absorption spectrum, which improves the short-circuit current density. A high conversion efficiency of 6.28% was obtained in simple devices (CP2 : PC61 BM 1: 1) which is one of the best results in the current literature for cyanopyrid-2, 6-dione-based small molecule donors. Graphical abstract: Image 1 Highlights: The first report of cyanopyrid-2, 6-dione (CP) functionality comprising 4-hexyloxyaniline to generate a novel donor targetCP2 . CP2 afforded improved thermal stability and blend morphology when compared with its structural analogueCP1 . Improvement of short-circuit current density and overall device performance using the newly designed CP unit. PCE >6% is among the highest efficiency numbers for CP-based small molecule donors.